Effect of Corncob Derived Biochar on Microbial Electroremediation of Dye Wastewater and Bioenergy Generation. Issue 31 (20th August 2020) - Sonu, Kumar; Sogani, Monika; Syed, Zainab; Dongre, Aman; Sharma, Gopesh
Abstract: This paper describes the potential of waste biomass derived biochar for improvement in the dye wastewater treatment in a microbial fuel cell (MFC). The complete MFC, an energy generating unit, was made with the waste products in order to demonstrate that low cost alternatives are available to replicate the positive results. Waste corncob derived biochar produced after acid modification has been evaluated as a supplement in an MFC for treatment of real dye wastewater (RDW). The two doses of sulfuric acid modified corncob biochar (SA‐MCB), (0.5 g and 1 g) and a blank (without any dose) were assessed for the effect on MFC performance. The maximum power density (49.92 W/m 2 ), current density (0.28 A/m 2 ), COD removal efficiency (88.39%), decolorization efficiency (81.6%) and TDS reduction (84.4%) were obtained with 0.5 g biochar dose. The Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) analysis revealed the structural changes occurring on the SA‐MCB after use in the MFC. The SEM analysis revealed the better biofilm formation due to SA‐MCB deposition. Power density with 0.5 g of SA‐MCB dose improved to more than 24 times in comparison to the system without any such dose. The UV spectrophotometer analysis confirmed the azo bond deformation during treatment. The overall results suggest that the use of SA‐MCB biochar as anode material and as a supplement in the MFC system may provide an effective anode‐biofilm in MFCs for wastewater treatment. Abstract : Impacts of acid modification on corncob biochar for its use as a supplement in the microbial fuel cell (MFC) were studied. Substantial improvement of using sulfuric acid modified corncob biochar (SA‐MCB) was observed on dye removal and power generation using real dye wastewater in MFC. High COD removal efficiency of 88.39% and decolorization efficiency of 81.6% were obtained. Power density with 0.5 g of SA‐MCB biochar improved to more than 24 times in comparison to the system without any such dose